In memory Oblivion Rogelia Cruz Martinez (Tzintzun, Revista de Estudios Históricos, 2016)
The murder of Rogelia Cruz Martinez, in January 1968, was part of the Guatemalancounterinsurgency practices. The image of this woman emphasized the no-limitslaw enforcement operations against the revolutionaries, the impact is imminentin the population, since a decade earlier she had held the title of Miss Guatemala1959 and participated in the Miss Universe in Long Beach, California. She waspart of one of the first revolutionary organizations of Guatemala, the Rebel ArmedForces, at the time of his abduction that took her to be killed cruelly. The imageof Rogelia Cruz was part of the Guatemalan revolutionary political ideology, in1973, the artist Arnold “El Tecolote” Ramirez Amaya painted a portrait of her inthe walls of the university campus during the so called muralización. Also, variouspolitical organizations have taken her name, however, the story lies in the wordingof a martyr, necessary for the mobilization and awareness of the fight, but far fromhistorical reality. Therefore, this is an attempt to delve into the lives of RogeliaCrruz to assist in the historical memory of Guatemala, from the contribution of awoman who made a significant contribution to the revolutionary process of theCentral American country.
Keywords: Rogelia Cruz; Guatemala; Weapon of War; Rebel Armed Forces; Guerrilla